ORGANIZATIONAL COMMITMENTS ARE MEDIATION OF RELATIONSHIPS BETWEEN SERVANT LEADERSHIP AND EMPLOYEE PERFORMANCE - Setyaningrum, Retno Purwani; Setiawan, Margono; Surachman, Surachman (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study was to observe the relationship between servant leadership, organizational commitment, and employee performance. In addition, this research also aims to observe variables servant leadership, organizational commitment, and employee performance. Empirical studies to test the servant leadership model can be done in the environment of nonprofit organizations and profits. Several studies that have been studied about the success of servant leadership have been achieved in nonprofit companies; therefore, the results of this study can be researched eligible for adoption by profit companies. This research is included in qualitative descriptive research, which explains the relationship between servant leadership to organizational commitment, and employee performance. The results of this study showed that servant leadership has relevance to organizational commitment, and employee performance. In addition, the results of this study showed that organizational commitment can mediate the relationship between servant leadership and employee performance.